2016
DOI: 10.1007/s10637-016-0395-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of infusion reactions to anti-neoplastic agents in early phase clinical trials: The MD Anderson Cancer Center experience

Abstract: Background Infusion reactions (IRs) to anti-neoplastic agents require prompt recognition and immediate treatment to avert significant complications. Methods We conducted a retrospective review of the medical records of consecutive patients who received anti-neoplastic therapy in the outpatient treatment center of the Department of Investigational Cancer Therapeutics from January 1, 2013 to November 30, 2013. Results Of the 597 patients who received treatment, 9 (1.5%) had IRs (all ≤ grade 2). The most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
0
3
0
1
Order By: Relevance
“…Up to 10% of documented hypersensitivity infusion reactions are severe, resulting in prolonged hospitalization and anaphylaxis treatment. [6][7][8][9] Training and experience responding to hypersensitivity reactions can significantly affect patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Up to 10% of documented hypersensitivity infusion reactions are severe, resulting in prolonged hospitalization and anaphylaxis treatment. [6][7][8][9] Training and experience responding to hypersensitivity reactions can significantly affect patient outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Among 597 patients receiving anticancer therapies in early-phase clinical trials at the Department of Investigational Cancer Therapeutics of MD Anderson Cancer Center from January to November 2013, 1.5% ( n = 9) experienced an IRR of grade ≤ 2. 10 All IRRs were reversible with appropriate symptomatic treatment, and seven of the nine patients who experienced an IRR were able to complete treatment after temporary cessation of infusion. A retrospective chart review of 197 breast cancer patients who received trastuzumab showed an incidence of IRRs corresponding to 16.2% of patients and 1.8% of administered doses.…”
Section: Introductionmentioning
confidence: 88%
“…Since the observation of reduced efficiency of chemotherapy in 22 types of neoplasms in 2004, where the "overall contribution of curative and adjuvant cytotoxic chemotherapy to 5-year survival in adults was estimated at 2.3% in Australia and 2.1% in the USA" [90], several works have warned about its high toxicity, with possible anticipation of death in patients treated in this way Chemotherapy brings about various side effects; cancer attack depends on there being no deviations of attack signals, which could lead to an increase in cytokine storms [97][98] [99]. Among these effects is Chemotherapy-Induced Peripheral Neuropathy (CIPN), which includes the symptom of cramp frequency.…”
Section: The Toxicity Of Various Chemotherapiesmentioning
confidence: 99%